SURG-05. Survival and functional outcomes in pediatric thalamic and thalamopeduncular low grade gliomas. (3rd June 2022) - Benes, Vladimir; Zapotocky, Michal; Liby, Petr; Taborsky, Jakub; Blazkova Jr., Jana; Blazkova Sr., Jana; Sumerauer, David; Misove, Adela; Pernikova, Ivana; Kyncl, Martin; Krskova, Lenka; Koblizek, Miroslav; et al.
Abstract: BACKGROUND: Childhood thalamopeduncular gliomas arise at the interface of thalamus and cerebral peduncle. The optimal treatment is total resection but not at the cost of neurological function. We present long-term clinical and oncological outcomes of maximal safe resection. METHODS: Retrospective review of prospectively collected data: demography, symptomatology, imaging, extent of resection, surgical complications, histology, functional and oncological outcome. RESULTS: During 16-year period (2005-20) 21 patients were treated at our institution. These were 13 girls and 8 boys (mean age 7.6 years). Presentation included progressive hemiparesis in 9 patients, raised intracranial pressure in 9 patients and cerebellar symptomatology in 3 patients. The tumor was confined to the thalamus in 6 cases. Extent of resection was judged on postoperative imaging as total (6), near-total (6) and less extensive (9). Surgical complications included progression of baseline neurological status in 6 patients, 5 of these gradually improved to preoperative status. All tumors were classified as low-grade gliomas. Disease progression was observed in 9 patients (median progression free survival 7.3 years). At last follow-up (median 6.1 years) all patients were alive; median Lansky score of 90. Seven patients were without evidence of disease, 6 had stable disease, 7 stable following progression and 1 had progressive disease managed expectantly. CONCLUSION: Pediatric patients with low grade thalamopeduncular gliomas have excellent long-term functional and oncological outcomes even when gross total resection is not achievable. Surgery should aim at total resection; however neurological function should not be endangered due to excellent chance for long-term survival.